Evaluation of Mentha arvensis essential oil and its major constituents for fungitoxicity - Makkar, Manpreet Kaur (J Food Sci Technol, 2018)
Essential oil and major constituents of menthe were evaluated for fungicidal activities. Gas chromatography–mass spectrometry (GC–MS) of essential oil from leaves of Mentha arvensis cv. CIM-Saryu revealed that menthol was found in highest amount (77.94%) followed by isomenthone (5.24%), neomenthyl acetate (5.18%) and menthone (5.00%). Menthol and menthone were extracted from the essential oil by column chromatography. Essential oil, menthol and menthone were screened for their fungicidal activity against Rhizoctonia solani and Fusarium moniliforme. Menthol was highly effective as compared to essential oil as well as menthone. All of them exhibited less activity than standard bavistin at all the tested concentrations.